PREVALENCE OF OSTEOARTHRITIS AMONG POSTMENOPAUSAL WOMEN IN MAHARASHTRA: A CROSS-SECTIONAL STUDY - Nidhi Suresh Sharma; Vikas Kumar Lamba (The Bioscan, 2024)
Background: Osteoarthritis (OA) is a leading cause of pain and disability among postmenopausal women, with hormonal decline, aging, lifestyle, and nutritional factors contributing to its high prevalence. In Maharashtra, cultural practices such as squatting, floor sitting, and high parity may further increase OA risk. However, region-specific prevalence data remain limited. Aim: To determine the prevalence of osteoarthritis among postmenopausal women in Maharashtra and examine associated demographic, lifestyle, and clinical risk factors. Methodology: A cross-sectional study was conducted among 300 postmenopausal women aged ≥45 years. Data on demographics, menopausal history, lifestyle factors, and clinical characteristics were collected through structured interviews. OA diagnosis and grading were determined using clinical assessment and Kellgren–Lawrence criteria. Descriptive statistics and chi-square tests were used to analyze associations between risk factors and OA prevalence.